Literasi Zakat Compliance Bagi Muzakky Pedagang Garmen - Fauzia, Ika Yunia; Pertiwi, Tanza Dona (Journal of Business & Banking, 2022)
For the garment merchants in Indonesia, who have the obligation to pay alm, zakat compliance literacy is very important. This study focuses on this issue and stamps from the fact that most pof them missunderstood the concept of zakat -both weatlh and trade- and its aplication. This research aims at exploring the zakat compliance literacy among these merchants in away that maybe appropiated by traders, business community and researchers a liked. This research uses qualitative method, with the modle of case study. More than twenty garment merchants in Indonesia are interviewed, 11 among whom are qualified as informants. The research finds, first: that a most garment merchant in Indonesia are zakat-literate, particulary as far as wealh-zakat is concerned; second, most garment merchant had paid their zakat, some of whom paid even more than they are supposed to do so: third, the way that zakat is distributed is closely related to the way this merchant understand their religion. Merchant with religious background tend to distribute their zakat on their own rather than giving it a through zakat-institution. The practical implication of this research is that there is a need for synergy between BAZNAS and traders to create facilities/media that can facilitate business actors in calculating trade zakat and its payments.